2008
DOI: 10.1002/jsfa.3162
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and microbial stability of high moisture dried apricots during storage

Abstract: BACKGROUND: This study was conducted to determine the chemical and microbial stability of high moisture (HM) dried apricots during storage at 5, 20 and 30• C for a period of 8 months. HM dried apricots were obtained by rehydrating dried apricots in 'water' and 'water+H 2 O 2 '.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Apricot fruits are regarded as a rich source of carotenoids, especially β-carotene, which represents more than 50% of the total carotenoid content (Radi et al, 1997;Sass-Kiss et al, 2005;Sağırlı et al, 2008). In addition to β-carotene, apricot fruit and its products contain smaller amounts of α-carotene, γ-carotene, zeaxantin and lutein (Fraser & Bramley, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Apricot fruits are regarded as a rich source of carotenoids, especially β-carotene, which represents more than 50% of the total carotenoid content (Radi et al, 1997;Sass-Kiss et al, 2005;Sağırlı et al, 2008). In addition to β-carotene, apricot fruit and its products contain smaller amounts of α-carotene, γ-carotene, zeaxantin and lutein (Fraser & Bramley, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…MC clearly showed that brown colour formation was highly dependent on storage temperature. Similarly, Sağırlı et al (2008) found k values as 0.0488 and 0.2411/month for brown colour formation in sulfitted (1458 mg/kg) dried apricots stored at 20 and 30 C at 36.6% MC, respectively. In another study with lower MC (18.9-24.5%), Türkyılmaz et al (2012) reported k values for sulfitted (188-3864 mg/kg) dried apricots stored at 20 and 30 C as 0.0193 and 0.0553/month, respectively.…”
Section: Brown Colour Formationmentioning
confidence: 81%
“…Therefore, brown-colour formation in NSDAs would not fit zero-order reaction kinetic model. Most studies in sulfite-dried apricots during storage showed that brown colour formation was fitted to a first-order reaction model (Sadler et al 1990;Sağırlı et al 2008;Türkyılmaz et al 2012).…”
Section: Brown Colour Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The browning degree of the dried apricots was determined as previously described (Saǧırlı et al, 2008) with some revisions.…”
Section: Evaluation Of Quality Parameters During Posttreatment Storagementioning
confidence: 99%